O que nos faz felizes? uma análise dos antecedentes do bem-estar subjetivo a partir da abordagem integrativa da satisfação com a vida - Figueira, Rebeca Formiga (2022)
Happiness is considered the greatest good of all and the ultimate motivation to human actions. However, scientists have been ignoring for decades the subjective well-being (SWB) of people. It is only since the 1980s that theoretical and empirical work has emerged. The study of SWB from a marketing perspective is recent. It was proposed by Gibbs in 2004, where the author considers that marketing can be channeled to replace trivial aspects of consumer satisfaction with the notion of personal flourishing. In this replacement, studies and marketing actions should focus on people's well-being as a sustainable phenomenon for humanity. That said, the goal of this work is to analyze the psychological factors and the domain of material well-being that influence the affective and cognitive components of subjective well-being. Therefore, a theoretical framework is presented and a theoretical model of SWB based on the Integrative Theory of life satisfaction is elaborated. The constructs that are part of this thesis are: personality traits (Big Five), gratitude, optimism, resilience, self-efficacy, materialism, financial well-being, anxiety-state, affection (positive and negative) and life satisfaction. The data collection took place in July 2020 through the google forms platform and a sample of 714 valid respondents was obtained. As this is a quantitative research, descriptive statistical analysis was performed; psychometric analysis and the multivariate analysis called Structural Equation Modeling (SEM). Finally, the results of this study support the proposed theoretical model and its results seem useful to contribute to advances in the theory and practice of marketing and in the subjective well-being of individuals.